2021
DOI: 10.3390/pathogens10121607
|View full text |Cite
|
Sign up to set email alerts
|

Clostridium perfringens-Induced Host-Pathogen Transcriptional Changes in the Small Intestine of Broiler Chickens

Abstract: Clostridium perfringens is an important opportunistic pathogen that may result in toxin-mediated diseases involving food poisoning/tissue gangrene in humans and various enterotoxaemia in animal species. It is a main etiological agent for necrotic enteritis (NE), the most financially devastating bacterial disease in broiler chickens, especially if raised under antibiotic-free conditions. Importantly, NE is responsible for losses of six billion US dollars annually in the global poultry industry. To investigate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…NE triggers an inflammatory response in the intestines of birds [ 32 ] and dysbiosis [ 33 , 34 ], causing energy imbalance and alteration in skeletal muscle growth [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…NE triggers an inflammatory response in the intestines of birds [ 32 ] and dysbiosis [ 33 , 34 ], causing energy imbalance and alteration in skeletal muscle growth [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to Huang et al [ 47 ] NE lesion scores are higher after one day of CP challenge and the lesions are mild at seven days. After infection with CP, the organism modulates strategies, upregulating protein components, to maintain intestinal integrity and reduce the damage caused by the bacteria [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…As reported, both CBD and nano-Se manifest direct and indirect actions on the same mechanisms of the gut physiological status, particularly the modulation of gut bacterial composition and activities; thus, we speculated that both CBD and nano-Se could be more effective in supporting gut integrity and should thus affect meat properties, especially in challenged birds, as this condition leads to fermentation disturbance, as proven in various models [27][28][29]. For instance, chickens challenged with C. perfringens were shown to have a higher abundance of several foodborne pathogens in the gut, including C. jejuni, E. coli and L. monocylogenes; this treatment also affected the transcript levels of many genes regulating host metabolism [30]. In our previous study [31], in a turkey model, we found that challenging birds with C. perfringens had a significant effect on the sarcoplasmic protein profile of the breast muscle, indicating a strong association between C. perfringens infection and the function of glycolytic enzymes in turkeys, which could lead to significant consequences in cell metabolism [32].…”
Section: Introductionmentioning
confidence: 99%
“…In a study on a meat duck model, it was found that under E. coli -LPS inflammation, there were significant alterations in the cecal microbiota as well as produced SCFAs 15 . In a study on a chicken model, infection with C. perfringens caused an increase in the host gut abundance of several foodborne pathogens, including C. jejuni , E. coli and L. monocylogenes, and affected the transcript levels of a number of genes regulating host metabolism 16 . In another study, a close correlation between cecal C. perfringens and C. jejuni was shown, indicating a potential influence on the final product quality 17 .…”
Section: Introductionmentioning
confidence: 99%